2004
DOI: 10.1002/cne.20262
|View full text |Cite
|
Sign up to set email alerts
|

Projections from the superior colliculus to the trigeminal system and facial nucleus in the rat

Abstract: To determine the influence of the superior colliculus (SC) in orienting behaviors, we examined SC projections to the sensory trigeminal complex, the juxtatrigeminal region, and the facial motor nucleus in rats. Anterograde tracer experiments in the SC demonstrated predominantly contralateral colliculotrigeminal projections. Microinjections in the deep layers of the lateral portion showed labeled nerve fibers and terminals in the ventromedial parts of the caudal principal nucleus and of the rostral oral subnucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…These findings are in harmony with previous studies, showing PAG-dorsal raphe nucleus connections and reciprocal connections between PAG and both the principal trigeminal nucleus and spinal trigeminal nucleus (Li et al, 1993a,b,c;Davergne et al, 2004). In addition, a previous report demonstrated that PAG neurons strongly innervate the rostromedial pericoerulear region, including Barrington's nucleus (Ennis et al, 1991).…”
Section: Discussionsupporting
confidence: 90%
“…These findings are in harmony with previous studies, showing PAG-dorsal raphe nucleus connections and reciprocal connections between PAG and both the principal trigeminal nucleus and spinal trigeminal nucleus (Li et al, 1993a,b,c;Davergne et al, 2004). In addition, a previous report demonstrated that PAG neurons strongly innervate the rostromedial pericoerulear region, including Barrington's nucleus (Ennis et al, 1991).…”
Section: Discussionsupporting
confidence: 90%
“…Studies have revealed connections (in humans and in cats) between motor, mesencephalic, main and spinal nuclei of the trigeminus and vestibular and oculomotor nuclei (Pinganaud et al, 1999), dorsal and ventral horn of the cervical spinal cord (C1eC5) (Buisseret-Delmas and Buisseret, 1990), prepositus nucleus of the hypoglossus, cerebellum (Pinganaud et al, 1999), superior colliculus and many brainstem nuclei (nucleus of the solitary tract, dorsal reticular formation, cuneate nucleus) (Marfurt and Rajchert, 1991;Pompeiarto et al, 1992;Dauvergne et al, 2004). All the anatomical connections mentioned above suggest that portions of the trigeminal system strongly influence the coordination of posture.…”
Section: Discussionmentioning
confidence: 99%
“…The centering of the vibrissal tips about the eyes may represent a peripheral correlate of the neural registration of the tactile and visual systems found in structures such as the superior colliculus (McHaffie and Stein, 1982;Dauvergne et al, 2004;Bezdudnaya and Castro-Alamancos, 2011). This geometric arrangement will inherently tend to ensure that tactile and visual modalities operate within the same coordinate system and bring tactile and visual maps into registration.…”
Section: Discussion Shape Of the Array Around The Face At Rest And Dumentioning
confidence: 99%